A direct and soft synthesis of biomimetic imprints in a stationary phase via sol-gel polymerization of silylated amino acids for selective separation of proteins - Yoann Ladner; Margaux Clavié; Jérémie Gouyon; Tristan Corbalan; Raquel Gutiérrez-Climente; Giang Ngo; Pascal Etienne; Philippe Rondard; Pierre-André Lafon; Pascal Dumy; Pierre Martineau; Martine Pugnière; et al. (Analytica Chimica Acta, 2026)

Analysis of Iguanodon bernissartensis teeth and bones using in-situ trace element, oxygen and strontium isotope composition: Implication for paleoecology, paleoenvironment and diagenesis - Sophie Decrée; Thierry Leduc; Pascal Godefroit; Etienne Deloule; Nolwenn Coint; Magdalena H. Huyskens; Eduardo T. Mansur; Vinciane Debaille; Jean-Marc Baele (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Impact of pea-wheat intercropping on grain ionome in relation with changes in Pseudomonas spp. and Enterobacterales abundances - Amélie Semblat; Cem Turanoglu; Céline Faivre-Primot; Jean-Paul Lemaître; Damien Marchand; Valérie Dufayet; Patrice Rouet; Laure Avoscan; Sylvie Mazurier; Philippe Lemanceau; Etienne-Pascal Journet; Barbara Pivato (Plant and Soil, 2025)

Modelling light-sharing in agrivoltaics: the open-source Python Agrivoltaic Simulation Environment (PASE 1.0) - Roxane Bruhwyler; Nicolas De Cock; Pascal Brunet; Jonathan Leloux; Pierre Souquet; Etienne Perez; Etienne Drahi; Sebastian Dittmann; Frédéric Lebeau (Agroforestry Systems, 2024)

Optimal species proportions, traits and sowing patterns for agroecological weed management in legume–cereal intercrops - Pierre Lebreton; Laurent Bedoussac; Catherine Bonnet; Etienne-Pascal Journet; Eric Justes; Nathalie Colbach (European Journal of Agronomy, 2024)

Demography of endangered juvenile green turtles in face of environmental changes: 10 years of capture-mark-recapture efforts in Martinique - Pierre Lelong; Aurélien Besnard; Marc Girondot; Caroline Habold; Fabienne Priam; Mathieu Giraudeau; Guillaume Le Loc'h; Aurélie Le Loc'h; Pascal Fournier; Christine Fournier-Chambrillon; Paco Bustamante; Sophie M. Dupont; et al. (Biological Conservation, 2024)

Pyruvate dehydrogenase kinase/lactate axis: a therapeutic target for neovascular age-related macular degeneration identified by metabolomics - Vincent Lambert; Sylvain Hansen; Matthieu Schoumacher; Julie Lecomte; Justine Leenders; Pascale Hubert; Michael Herfs; Silvia Blacher; Oriane Carnet; Cassandre Yip; Pierre Blaise; Edouard Duchateau; et al. (Journal of Molecular Medicine, 2020)

Long‐term influence of early human occupations on current forests of the Guiana Shield - Guillaume Odonne; Martijn van den Bel; Maxime Burst; Olivier Brunaux; Miléna Bruno; Etienne Dambrine; Damien Davy; Mathilde Desprez; Julien Engel; Bruno Ferry; Vincent Freycon; Pierre Grenand; et al. (Ecology, 2019)
To decipher the long‐term influences of pre‐Columbian land occupations on contemporary forest structure, diversity, and functioning in Amazonia, most of the previous research focused on the alluvial plains of the major rivers of the Amazon basin. Terra firme, that is, nonflooded forests, particularly from the Guiana Shield, are yet to be explored. In this study, we aim to give new insights into the subtle traces of pre‐Columbian influences on present‐day forests given the archaeological context of terra firme forests of the Guiana Shield. Following archaeological prospects on 13 sites in French Guiana, we carried out forest inventories inside and outside archaeological sites and assessed the potential pre‐Columbian use of the sampled tree species using an original ethnobotanical database of the Guiana Shield region. Aboveground biomass (320 and 380 T/ha, respectively), basal area (25–30 and 30–35 m 2 /ha, respectively), and tree density (550 and 700 stem/ha, respectively) were all significantly lower on anthropized plots (As) than on nonanthropized plots ( NA s). Ancient human presence shaped the species composition of the sampled forests with Arecaceae, Burseraceae, and Lauraceae significantly more frequent in As and Annonaceae and Lecythidaceae more frequent in NA s. Although alpha diversity was not different between As and NA s, the presence of pre‐Columbian sites enhances significantly the forest beta diversity at the landscape level. Finally, trees with edible fruits are positively associated with pre‐Columbian sites, whereas trees used for construction or for their bark are negatively associated with pre‐Columbian sites. Half a millennium after their abandonment, former occupied places from the inner Guiana Shield still bear noticeable differences with nonanthropized places. Considering the lack of data concerning archaeology of terra firme Amazonian forests, our results suggest that pre‐Columbian influences on the structure (lower current biomass), diversity (higher beta diversity), and composition (linked to the past human tree uses) of current Amazonian forests might be more important than previously thought.

Abundance and Impact on Soil Properties of Cathedral and Lenticular Termite Mounds in Southern Indian Woodlands - Pascal Jouquet; Etienne Airola; Nabila Guilleux; Ajay Harit; Ekta Chaudhary; Séraphine Grellier; Jean Riotte (Ecosystems, 2017)

Phosphorus availability and microbial community in the rhizosphere of intercropped cereal and legume along a P-fertilizer gradient - Xiaoyan Tang; Sarah A. Placella; Florent Daydé; Laetitia Bernard; Agnès Robin; Etienne-Pascal Journet; Eric Justes; Philippe Hinsinger (Plant and Soil, 2016)

Effect of activated charcoal on multiplication of African yam (Dioscorea cayenensis-rotundata) nodal segments using a temporary immersion bioreactor (RITA®) - Frederik Polzin; Isabelle Sylvestre; Eveline Déchamp; Pascal Ilbert; Hervé Etienne; Florent Engelmann (In Vitro Cellular & Developmental Biology - Plant, 2014)

Real-time investigation of the muco-adhesive properties of Lactococcus lactis using a quartz crystal microbalance with dissipation monitoring - Doan Thanh Lam Le; Sandrine Zanna; Isabelle Frateur; Philippe Marcus; Pascal Loubière; Etienne Dague; Muriel Mercier-Bonin (Biofouling, 2012)

Sexually transmitted bacteria affect female cloacal assemblages in a wild bird - Joël White; Pascal Mirleau; Etienne Danchin; Hervé Mulard; Scott A. Hatch; Philipp Heeb; Richard H. Wagner (Ecology Letters, 2010)
Ecology Letters (2010) 13: 1515–1524 Abstract Sexual transmission is an important mode of disease propagation, yet its mechanisms remain largely unknown in wild populations. Birds comprise an important model for studying sexually transmitted microbes because their cloaca provides a potential for both gastrointestinal pathogens and endosymbionts to become incorporated into ejaculates. We experimentally demonstrate in a wild population of kittiwakes ( Rissa tridactyla ) that bacteria are transmitted during copulation and affect the composition and diversity of female bacterial communities. We used an anti‐insemination device attached to males in combination with a molecular technique (automated ribosomal intergenic spacer analysis) that describes bacterial communities. After inseminations were experimentally blocked, the cloacal communities of mates became increasingly dissimilar. Moreover, female cloacal diversity decreased and the extinction of mate‐shared bacteria increased, indicating that female cloacal assemblages revert to their pre‐copulatory state and that the cloaca comprises a resilient microbial ecosystem.

The Medicago truncatula SUNN Gene Encodes a CLV1-like Leucine-rich Repeat Receptor Kinase that Regulates Nodule Number and Root Length - Elise Schnabel; Etienne-Pascal Journet; Fernanda de Carvalho-Niebel; Gérard Duc; Julia Frugoli (Plant Molecular Biology, 2005)

Horizontal Gene Transfer of ?Prototype? Nramp in Bacteria - Etienne Richer; Pascal Courville; Isabelle Bergevin; Mathieu F. M. Cellier (Journal of Molecular Evolution, 2003)